ANALYSIS OF INCENTIVE, WORK DISCIPLINE, AND EDUCATION LEVELS THAT INFLUENCE EMPLOYEE PERFORMANCE - Juliani, Tania; Windu, Felik Sad (Universitas Brawijaya, Indonesia, 2017)
This study aims to determine the effect of incentives, work discipline, and level of education both simultaneously and partially to the performance of employees of PT. Wahana Ottomitra Multiartha, Tbk Blitar city branch. The subject of this research is the employees of the marketing division as much as 40 respondents. Data analysis technique used is multiple linear regression analysis. The results of this study indicate that the contribution of incentive variable, work discipline, and education level have positive influence simultaneously. F test results indicate if the variables of incentive, work discipline, and level of education simultaneously have a significant effect on employee performance. The result of t test is known if incentive variable, work discipline, and education level partially have a significant effect on employee performance. The result of multiple regression analysis shows that if all the regression coefficients are positive, there is a positive influence of incentive variable, work discipline, and education level with employee performance variable. From these results, indicate that work discipline variable has the greatest regression coefficient value. It means that employee performance variable is more influenced by work discipline variable. If work discipline is increasing, then employee performance will increase as well.